2014
DOI: 10.1089/mdr.2014.0019
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Amoxicillin Resistance ofHelicobacter pyloriIn Vitro: Characterization of Resistance Mechanisms

Abstract: Helicobacter pylori is the major cause of peptic ulcers and gastric cancer in humans. Treatment involves a two or three drug cocktail, typically including amoxicillin. Increasing levels of resistance to amoxicillin contribute to treatment failures, and higher levels of resistance are believed to be due to multiple genetic mutations. In this study, we examined the progression of spontaneous genetic mutations that contribute to amoxicillin resistance in H. pylori when exposed to increasing concentrations of amox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 36 publications
2
36
1
1
Order By: Relevance
“…In combination with the amino acid substitutions of pbp1, hopB and hopC, mutations confer further AMX resistance [60]. A later study, however, did identify hefC as important here and was interpreted to mean that mutations in pbp1, hefC, hopC, hofH, and possibly pbp2 contribute to high-level resistance to AMX [65]. As omp25 acts as a porin, this change may be involved in increased AMX efflux as well [62,63].…”
Section: Resistance To Nitroimidazoles: Mnzmentioning
confidence: 74%
“…In combination with the amino acid substitutions of pbp1, hopB and hopC, mutations confer further AMX resistance [60]. A later study, however, did identify hefC as important here and was interpreted to mean that mutations in pbp1, hefC, hopC, hofH, and possibly pbp2 contribute to high-level resistance to AMX [65]. As omp25 acts as a porin, this change may be involved in increased AMX efflux as well [62,63].…”
Section: Resistance To Nitroimidazoles: Mnzmentioning
confidence: 74%
“…In an interesting study, H. pylori cultured in the presence of cholesterol became resistant to bile salts and their analogs, and this phenotype required the HefC pump (688). Intriguingly, hefC missense mutations were among the several gene mutations in in vitro-selected isolates with high-level resistance to amoxicillin, and the introduction of a mutated allele to the wild type increased resistance (689). Through examining the whole-genome sequences of clarithromycin-resistant isolates, a new study revealed the gene clusters of TolC homologs involved in clarithromycin susceptibility profiles in individual isolates (690).…”
Section: Helicobacter Sppmentioning
confidence: 99%
“…Expression of active efflux pumps that excrete drugs and point mutations in the pbp1A gene may contribute to the mechanisms of resistance to beta‐lactams. Other mutations such as pbp2, hefC, hopC and hofH have been identified among H. Pylori ‐resistant strains …”
Section: Antibiotic Resistance Mechanismsmentioning
confidence: 99%